2018
DOI: 10.3390/app8040511
|View full text |Cite
|
Sign up to set email alerts
|

Towards an ICT-Based Platform for Type 1 Diabetes Mellitus Management

Abstract: Type 1 Diabetes Mellitus (DM1) is a metabolic disease that is characterized by chronic hyperglycemia due to a lack of pancreatic insulin production. This forces patients to perform several blood glucose measurements per day-by means of capillary glucometers-in order to infer a trend and try to predict future values. In this way, a decision about the insulin dosage that has to be exogenously injected to maintain glycemia within the desirable levels is made. Unfortunately, this method usually suffers from relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
0
20
0
5
Order By: Relevance
“…Rodriguez-Rodriguez et al revealed that recent technologies, such as IoT, big data, cloud computing, novel biosensors, and machine learning can perform significant part in improving the diabetes management [38]. The previous studies have shown significant results with the implementation of IoT in healthcare systems.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Rodriguez-Rodriguez et al revealed that recent technologies, such as IoT, big data, cloud computing, novel biosensors, and machine learning can perform significant part in improving the diabetes management [38]. The previous studies have shown significant results with the implementation of IoT in healthcare systems.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The possibilities of a remote blood glucose monitoring have also been exposed more recently in [ 78 ]. All of these issues have been specifically analyzed in a previous work of the authors [ 79 ], with an extended evaluation of the historical development of theses ICT-based platforms, their pros and cons, and a proposal of a complete diabetes telemedicine system in an ICT environment.…”
Section: Challenges To Be Overcomementioning
confidence: 99%
“…Given that the possibilities of ICT have been expanded by the Internet of Things (IoT) [4], new tools have emerged to manage and prevent the incidence of intimate partner and other types of gender-based violence. However, even though biosensors and other resources have had positive outcomes in healthcare [5], challenges remain to their use among IPV survivors seeking protection. In particular, previous trials have focused on finding means by which a victim of assault can set off an alarm; however, given the speed and unpredictability which characterize acts of IPV, most women do not have the chance to consciously activate a safety device.…”
Section: Introductionmentioning
confidence: 99%